DEVELOPING STUDENTS’ DIGITAL COMPETENCE IN TEACHING FOREIGN LANGUAGES (World Bulletin of Social Sciences, 2023)
Today, education aims not so much at obtaining new knowledge, but at mastering the competencies necessary in the life of each individual. Lifelong Learning is the continuous acquisition of new knowledge, skills and abilities through training courses, additional education programs, etc., and gaining experience from life itself. This article discusses the concept of digital competence in teaching English as foreign language and its components in accordance with the European Qualification Framework
Keywords: Information and communication competence; lifelong learning